Plan estratégico y de marketing para reposicionar la empresa “Estrategos Empresariales” en el mercado de Santo Domingo de los Tsáchilas, 2014 - Yánez Riofrio, María Cisne (2015)
The research was conducted in the Province of Santo Domingo de los Tsáchilas order to develop a strategic marketing plan and business strategists to reposition the company with specific objectives to identify acceptance with the services offered by the company, analyzing internal and external to the matrix Foda, The methods used in the investigation, Inductive allowed to draw general conclusions about the behavior of consumers in the market of Santo Domingo de los Tsáchilas, Statistical data collected were interpreted statistically and graphs for better understanding results, Analytics by analyzing understand the factors that influence the repositioning of the company. With the art of the interview that the company manager Mr Patrick Wilson Delgado was performed in order to know the advantages and disadvantages of market research instrument was a survey to potential customers. A sample of the economically active population carrying 382 surveys where information about the preferences of potential customers with the intention of meeting their needs was obtained was investigated. According to market research potential customers agree 89% with the services offered by the company and 96% prefer quality and speed at the time the action was requested. And a reduced market share (4%) due to ignorance of the company and 96% proficiency, potential customers because of their constant publicity prefer the company "Design and Advertising" according to research.